Lithological composition in deep geothermal source reservoirs of temperature 160 °C in the territory of Slovakia - BEZÁK, Vladimír; MAJCIN, Dušan (Contributions to Geophysics and Geodesy, 2018)
Our contribution presents the geological analysis results of the lithological composition for deep geothermal sources characterized by the thermal conditions suitable for application of classic hydrothermal sources exploitation and specialized EGS technologies for the electricity production in the territory of Slovakia. The results are presented in the form of lithological characterization for the isothermal surface depths with the reservoir temperature of 160 °C. The lithological conditions of geothermal source regions were constructed using available published and archive materials. From the point of view of technically utilized depths (up to 5000 m) there are two most perspective regions – Eastern Slovakia and Danube Basin with surrounding areas. We tried to characterize supposed lithological composition also in second category of geothermal sources between 5 and 6 km.